Penerapan Metode Multi-Objective Optimization on the Basis of Simple Ratio Analysis Dalam Seleksi Pengangkatan Karyawan Tetap - Lulu Dia Marito Sitompul; Keti Gabryriel Purba; Aripin, Soeb (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Improvement of status as a permanent employee is a form of career advancement for a contract employee. because permanent employees are the main asset for a company. In selecting permanent employees for a company, there are some employees who volunteer to take part in the selection to become permanent employees. permanent employee selection is carried out in stages such as file selection, oral or written tests and interviews. Usually the selected employees are sometimes far from what is expected, so it is necessary to use a decision-making system as the final result, so a decision support system is needed using the Multi-Objective Optimization on the Basis of Simple Ratio Analysis (MOOSRA) method. The application of the Multi-Objective Optimization on the Basis of Simple Ratio Analysis (MOOSRA) method used in the selection of permanent employees is to find the best employees in a company. Decision support systems are used to assist decision making to determine permanent employees. The results of this study can assist decision making in determining which employees are selected to become permanent employees. From the results of the calculation of the Multi-Objective Optimization on the Basis of Simple Ratio Analysis (MOOSRA) method, the selection of permanent employees is based on predetermined criteria, an employee named